Effect of Relative Humidity and Storage Temperature on the Behavior of Listeria monocytogenes on Fresh Vegetables. Issue 4 (31st October 2013) - Likotrafiti, Eleni; Smirniotis, Petros; Nastou, Aikaterini; Rhoades, Jonathan
Abstract The survival and growth of Listeria monocytogenes on fresh lettuce (Lactuca sativa), cucumber (Cucumis sativus) epidermis and parsley (Petroselinum sativum) under different relative humidity (RH) conditions and storage temperatures was studied. Inoculated vegetable pieces were stored at 10C for 7 days, 20C for 5 days, and 30C for 24 h, and at 53 and 90% RH. L. monocytogenes was enumerated periodically by plate count. L. monocytogenes did not grow on lettuce or parsley, but either declined in number or remained approximately constant. At cooler temperatures, a negative effect of low humidity on survival was observed. L. monocytogenes grew on cucumber epidermis at all three temperatures, increasing from around 4.0 to around 5.5 log cfu/cm2 when stored at 90% RH. Low RH negatively affected growth, limiting the increase to around 0.5 log cfu/cm2 in most cases. Practical Applications Fresh vegetables are increasingly important vehicles of foodborne pathogens. The majority of published studies on growth and survival of Listeria monocytogenes on vegetables have been conducted on lettuce leaves and few data are available on the influence of relative humidity (RH). Growth of L. monocytogenes may increase the risk to the consumer of some types of fresh vegetables. Maintaining lower RH during storage can decrease this risk, but may conflict with other product quality requirements. L. monocytogenes does not grow on undamaged leaf surfaces under the conditions tested: when reviewing the literature it is important to differentiate between whole and shredded/cut leaves.